Knowledge Accessibility and Regional Economic Growth - Charlie Karlsson; Martin Andersson; Urban Grasjo (European Regional Science Association (ERSA), 2006)
This paper analyzes the role of knowledge accessibility in re¬gional economic growth. The research question is the following: can the variation in knowledge accessibility between regions in a given period explain the variation in their growth performance in subsequent periods? As knowledge measures, we use company R&D, university R&D and patents. A main assumption in the paper is that knowledge accessibilities as a measure of knowledge potentials transform into potential knowledge flows. Our regression results indicate that the intra-municipal and intra-regional knowledge accessibilities of municipalities are significant and capable of ex¬plaining a significant share of the variation in growth of value added per employee between Swedish municipalities. However, the inter-regional knowledge accessibility of municipalities turned out to be insignificant. This is interpreted as a clear indication of spatial dependence in the sense that the knowledge resources in a given municipality tend to have a positive effect on the growth of another municipality, conditional on that the municipalities belongs to the same functional region. Thus, the results of the analysis indicate that knowledge flows transcend municipal borders, but that they tend to be bounded within functional regions. Also, the analysis shows that there is no remaining spatial correlation among the residuals of the spatial units (municipalities) when using accessibility measures in the model, which confirms that the spatial dependence is captured by the accessibility variables.
Keywords: 330